Cuộc thám hiểm không gian Zathura (Công ty Cổ phần phim Thiên Ngân, 2009)
In this heart-racing science fiction adventure, Zathura, two squabbling brothers are propelled into deepest, darkest space while playing a mysterious game discovered in the basement of their old house. On their fantastic journey, they are joined by a stranded astronaut and must survive meteor showers, hostile lizard-like aliens, a rocket-propelled robot who runs amok and an intergalactic spaceship battle. Unless they finish the game and reach the planet Zathura, they could be trapped in outer space forever.